Newspaper cutting : Observer : The British Note: Charges against Russia and Italy ; with handwritten resolution
015a_0015_001 THE BRITISH NOTE. CHARGES AGAINST RUSSIA AND ITALY. Details of the British Note circulated to members of the Non-Intervention Committee at the end of yesterday's meeting are now available. The gist of the statement is that the Committee has to consider infractions, and that no country should he unduly sensitive over charges made against it. The agreement had prevented the worsening of a dangerous international situation, and had put a brake on the supply of arms to Spain. The British Government, the Note states, is investigating the case of the British steamer Bramhill, which is alleged to have conveyed arms to Spain. Four cases of infractions of the agreement are given as follows:- (1) The Russian steamer Stari Bolshevik is alleged to have landed at Carthagena, on October 15, eighteen aeroplanes in parts, fifteen tanks and over 300 cases of bombs and other ammunition. (2) The Spanish steamer Campeche is alleged to have landed about a fortnight ago, at Carthagena, a number of guns, trench mortars, rifles, and other ammunition, all of Soviet origin. (3) The Russian steamer Chuschchev is alleged to have landed, on October 19, at Alicante, eighty-five military lorries of Russian origin. (4) Three Italian aeroplanes are alleged to have landed at Palma ( Majorca ), on October 7, while an Italian ship is alleged to have unloaded cases of armaments and munitions there about this date. — Reuter. Observer. Sunday 25 October. This meeting reaffirms the undoubted right of the Republican Govt. in Spain, to obtain the necessary means to suppress rebellion within its borders, and realising that the policy of non-intervention has not been effective, calls upon the British Government, in conjunction with the French Government, through international agreement to restore the full liberty of the Spanish Government to purchase arms. 292/946/15a/15